Historical increase in agricultural machinery weights enhanced soil stress levels and adversely affected soil functioning - Keller, Thomas; Sandin, Maria; Colombi, Tino; Horn, Rainer; Or, Dani (Soil & tillage research, 2019)
•Increase in farm vehicle weights has increased soil compaction levels.•Increasing compaction levels coincide with a stagnation in crop yields.•We speculate that the increasing compaction levels have increased flood events.•Compaction costs were estimated to several hundred M€ yr−1 for Sweden. Soil compaction caused by vehicular traffic adversely affects key soil functions and ecosystem services that soils provide. Although compaction is a well-recognized problem, it remains challenging to quantify the economic and ecological costs of compaction. The mechanization in agriculture has resulted in a steady increase in weight of farm vehicles. It is reasonable to assume that this has exacerbated soil compaction, but there is little quantitative knowledge on the development of compaction levels in arable soils. To quantify these trends, we use historical records of harvester and tractor weights to simulate how the weight increase has changed soil stresses and bulk density of arable soil, and to predict impacts on the mechanical resistance for root growth and on soil hydraulic properties. Our simulations show a clear increase in soil stress levels with higher bulk density and mechanical penetration resistance, and a decrease in soil hydraulic conductivity in agreement with available data. We show that increased mechanical resistance has resulted in decreased root elongation rates and consequently prolonged the time required for roots to reach a certain soil depth. The historical changes of compaction levels and associated limitations on root elongation rates coincide with a stagnation in crop yields in the 1990s observed for cereals in many countries. Our calculations illustrate that the historical increase in compaction levels has drastically decreased saturated hydraulic conductivity and water storage capacity of subsoils. We speculate that this has contributed to the increase in the incidence and severity of flood events during recent decades in Europe. Finally, we take Sweden as an example and estimate annual compaction costs due to agricultural productivity loss and flooding damage of several hundred M€ yr−1 for Sweden. Considering the continuation of upwards trends in the average weight of farm machinery and the projected increase in extreme weather events, the costs of soil compaction are likely to escalate. The study highlights that we have likely exceeded the acceptable loads, and that future agricultural operations must consider the inherent mechanical limit of soil.